Clinical profile and epidemiological characteristics of COVID-19 patients admitted in the district hospital of North India- a retrospective study - Gupta, Vishal; Bhagat, Shweta; Sharma, Vinod; Bala, Kiran; Kumar, Tejinder (International Journal of Research in Medical Sciences, 2023)
Background: During COVID-19 all the tertiary institutes were overburdened so all the peripheral institutes, mostly district hospitals were made functional to provide management to COVID-19 patients in moderate and severe cases. The study attempts to find out the clinical profile of admitted patients in one of the district hospital. Methods: Retrospective data was studied from records of district hospital Samba when it was chosen as COVID-19 dedicated hospital. Results: Record of 77 patients was studied and data was analyzed with the help of descriptive statistics. Chi square test was done to find out the association. Mean age was 56.8±16.19 years with male female ratio of 1.33:1. 50% males and 42.4% of females did not have any associated co-morbidities. Half of the studied participants were anemic. Conclusions: Study showed that patients admitted in hospital presented with variable presentation and associated co morbidities were significantly associated with mortality. Peripheral institutions should be equipped with all the facilities to cope with such public health emergencies.